PENERAPAN MODEL LEARNING CYCLE 5E BERBANTUAN VIDEO ANIMASI PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Sapina Sapina; Safriana Safriana; Fajrul Wahdi Ginting; Muliani Muliani; Tulus Setiawan (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to determine the increase in students' understanding of concepts on various energy materials and their changes through the Learning Cycle 5E learning model assisted by Learning Animation Videos. This study used a mixed method or mix methods type of concurrent embedded (unbalanced mixture), with a pretest-posttest control group design research design. Sampling technique with simple random sampling technique, the sample of this study was class X TKJ 2 students as an experimental class and class X DPIB as a control class with the number of each class was 20 students. The average N-Gain score for the control class was 0.37 including the medium category. The N-Gain score for the experimental class is 0.7 including the high category. The results of this study show that the application of the Learning Cycle 5E model assisted by learning animation videos can improve the understanding of the concepts of grade X students on various materials